New Estimates of Quality of Life in Urban Areas - Blomquist, Glenn C.; Berger, Mark C.; Hoehn, John P. (American Economic Review, 1988)
Implicit markets capture compensation for intraurban and interregional differe nces in amenities and yield differences in housing prices and wages. These pecuniary differences become preference-based weights in a qual ity-of-life index. Hedonic equations are estimated using microdata fr om the 1980 Census and assembled county-based amenity data on climati c, environmental, and urban conditions. Ranking of 253 urban counties reveals substantial variation within, as well as among, the 185 urba n areas. The quality-of-life differences across counties within one S MSA is almost one-half of the difference between the top- and bottom- ranked counties in the nation. Copyright 1988 by American Economic Association.